For whom the bell tolls eaudiobook - Hemingway, Ernest (Simon & Schuster Audio, 2006)
Ernest Hemingway's masterpiece on war, love, loyalty, and honor tells the story of Robert Jordan, an antifascist American fighting in the Spanish Civil War. In 1937 Ernest Hemingway traveled to Spain to cover the civil war there for the North American Newspaper Alliance. Three years later he completed the greatest novel to emerge from "the good fight" and one of the foremost classics of war literature. For Whom the Bell Tolls tells of loyalty and courage, love and defeat, and the tragic death of an ideal. Robert Jordan, a young American in the International Brigades, is attached to an antifascist guerilla unit in the mountains of Spain. In his portrayal of Jordan's love for the beautiful Maria and his superb account of a guerilla leader's last stand, Hemingway creates a work at once rare and beautiful, strong and brutal, compassionate, moving, and wise. Greater in power, broader in scope, and more intensely emotional than any of the author's previous works, For Whom the Bell Tolls stands as one of the best war novels ever written.